Biomassa dan Kandungan Nutrisi Artemia sp. yang Diberi Papakan Alami Thalassiosira sp. dan Chlorella sp. - Trisnabatin, Galang Alamin; Julyantoro, Pande Gde Sasmita; Wijayanti, Ni Putu Putri (Current Trends in Aquatic Science; Vol 4 No 1 (2021), 2021)
This study aims to determine the effect of giving Thalassiosira sp. and Chlorella sp. on the biomass and nutritional content of Artemia sp. This research was conducted at the Microalga Laboratory, Living Feed Unit of the Situbondo Aquaculture Aquaculture Fisheries Unit from June to August 2019. This research was experimental using a Completely Randomized Design (CRD) with three treatments and three repetitions. Provision of natural food against Artemia sp. carried out with 3 treatments namely Treatment (a) feeding Chlorella sp., (b) feeding with Thallassiosira sp., (c) feeding combination Thallassiosira sp. and Chlorella sp. combination feeding has a high nutrient content compared to treatments (a) and (b). The protein content in treatment (c) was 58.64% compared to treatment (a) amounted to 49.79% and treatment (b) 53.60%. Water quality measured during the study were temperatures ranging from 25.9-27 ° C, salinity values ??ranged from 34 to 38 ppt, pH values ??ranged from 8.04 to 8.45, and DO values ??ranged from 7.8 to 12.8 ppm. The value of water quality is still in the optimal range for the growth of Artemia sp.